Faunal remains from an Almohad (Ad XII/XIII) silo at the Castle of Aljezur (Portugal) - Mota, Diogo (2016)
The analysis of a faunal collection from a storage silo found in the castle of Aljezur, dating from the Almohad period (XII/XIIIth centuries AD), is presented. It appears that the community occupying the castle concentrated on hunting species such as the rabbit, wild boar, red deer and Iberian lynx, while evidences of stockbreeding were scarce and centered upon caprines with horses and chicken playing minor role. The presence of a large dog has been assumed to be an aid for hunting but possibly also in herd keeping. With the exception of the lynx, all large mammals evidenced traces of consumption. The domestic cat is taken to represent a pet whereas the lynx had probably a role as a fur provider. It should be noted that equids and the pond turtle were probably food items. Rodents are taken to represent commensals whereas the toad of the Genus Bufo probably represented an intrusive element.